The Khatajatra of Maitiajima - Parajuli, Sandhya Khanal (Nepalese Culture, 2025)
This paper analyzes a celebrated and jovial fair popularly known as Khatajatra of Maitidevi also known as Maitiajima. A Lichchavi inscription and several other monuments of the Lichchavi period exist within the temple premises of the goddess Maitidevi who is also worshipped as goddess Kumari among the Astamatrikas. Maitiajima is worshipped by both Hindu and Buddhist devotees. The daily rituals are carried out by a Buddhist Guvaju. Many festival and fairs are held in the name of the goddess. Khatajatra takes place on the fourth day of the dark fortnight of Kartik, beginning at Dhyochen of Maitiajima in Maligaunn. In this context, questions such as when the khatajatra of Maitiajima was introduced,who conducts it, how it is performed, and why it is observed are addressed here through a framed research. To uncover the facts, this qualitative research was conducted through the observation of khatajatra, interviews with experts, guthiyars, and priests, as well as consultations of literary sources. Since khata jatra begins at dhyochhen of Maitiajima in Maligaunn, the geographical scope of this research is delimited to Maligaun, Gyaneshwor, and Maitidevi, the route followed by the jatra. The paper reveals that the khatajatra of Maitiajima has been celebrated since the early medieval period by the Munikar guthiyars, who installed Goddess Maitiajima in their farmland and have cared for her since ancient times. It is celebrated over four days with three khatas representing Goddess Maitiajima, Ganesh, and the Astamatrikas.